Life satisfaction among farmers in paddy granaries in Malaysia - Terano, Rika; Mohamed, Zainal Abidin (Canadian Center of Science and Education, 2014)
The industrial policy that was undertaken by the Malaysian government has spurred economic development and prosperity for the last 3 decades. Nevertheless the economic development has been heavily concentrated on the west coast of Peninsular Malaysia, thus causing income disparity between urban and rural areas. The government has published a series of reports on Malaysian Quality of Life (QoL) since 2002. It measured QoL among Malaysian people narrowly from the material aspects of QoL. However, it is also very important to approach people's QoL not only from the material aspects but also from non-material aspect of QoL including happiness, satisfaction and desire and how they generally feel about their life. It would provide distinctive indicators among Malaysian people. This paper aims to approach life satisfaction weather people are satisfied with their life or not especially from both material and non-material aspects of QoL among Malaysian people living in two granary areas of Penang and Kelantan. A total of 80 respondents were interviewed by structured questionnaires, and binary logistic regression was used to determine the influential socio-demographic factors and important dimension of the QoL on life satisfaction. The result indicates that age, family size and four dimensions of QoL such as community, residential condition, economic level, and family/partner were important factors in influencing on life satisfaction. Especially, QoL in terms of community dimension was the most influential factor on life satisfaction.